2020
DOI: 10.1111/apa.15447
|View full text |Cite
|
Sign up to set email alerts
|

The Dutch well child language screening protocol for 2‐year‐old children was valid for detecting current and later language problems

Abstract: Aim A little is known about predictive validity of and professionals' adherence to language screening protocols. This study assessed the concurrent and predictive validity of the Dutch well child language screening protocol for 2‐year‐old children and the effects of protocol deviations by professionals. Methods A prospective cohort study of 124 children recruited and tested between October 2013 and December 2015. Children were recruited from four well child clinics in urban and rural areas. To validate the scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…Holzinger et al demonstrated, for two-year screening, that the parent report as stage 1 (followed by a stage 2 direct evaluation by the pediatrician limited to those failing at stage 1) resulted in good predictive validity of language delay, even one year after screening administration. This finding points to the effectiveness of screening instruments based on a combination of direct child assessment and proxy reports, in line with the recently reported results for a Dutch well child language screening protocol ( 1 ).…”
Section: Administration Of Proxy or Direct Screeningsupporting
confidence: 90%
“…Holzinger et al demonstrated, for two-year screening, that the parent report as stage 1 (followed by a stage 2 direct evaluation by the pediatrician limited to those failing at stage 1) resulted in good predictive validity of language delay, even one year after screening administration. This finding points to the effectiveness of screening instruments based on a combination of direct child assessment and proxy reports, in line with the recently reported results for a Dutch well child language screening protocol ( 1 ).…”
Section: Administration Of Proxy or Direct Screeningsupporting
confidence: 90%
“…Our findings of high predictive validity of the screening tool after 1 year confirm those of the few language screening tools in 2-year-old children that predict later language status. The Dutch well-child language screening protocol for 2-year-old children ( 29 ), which is based on direct-child assessment of word comprehension and parent reports (word combinations and playing behavior), yielded a slightly higher sensitivity (0.82) but lower specificity (0.74) to predict language problems 1 year later. However, about half of the validation sample were screening failures, and referral bias artificially increases sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In their systematic review on preschool screening tools for language and behavioral difficulties, Sim et al concluded that parent-reported screening tools for language in preschool aged children achieved higher sensitivity, specificity, and negative predictive value than direct child assessment ( 28 ). However, Visser-Bochane et al ( 29 ) reported high predictive validity for a screening instrument (van Wiechenschema) based on a combination of direct child assessment and parent report. Evaluations of parent-reported tools (MCDI and LDS) showed high specificity with moderate sensitivity, whereas the combined tool had poorer specificity but better sensitivity, and thus higher rates of prediction accuracy of children with language delays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…de Koning et al (2004) found relatively low sensitivity (24%–52%) but high specificity (97%). On the other hand, Visser-Bochane et al (2020) reported higher sensitivity (82%) but lower specificity (74%). These different findings might be due to several differences in methodology.…”
Section: Introductionmentioning
confidence: 93%